The Effect of Job Crafting and Resilience on the Adaptive Performance of Start-Up Developer Employees in Malang City - Sulistiyorini, Diyah; Safitri, Dewi Octaria (Universitas Negeri Malang, 2023)
The primary objective of this study is to investigate the impact of job crafting and resilience on adaptive performance within the context of start-up developers. The research methodology employed in this study is quantitative research. The study subjects consisted of a sample of 37 software developers residing in Malang City, ranging in age from 20 to 40 years old and possessing a minimum of one year of professional experience in the field. The hypothesis is tested using multiple linear regression. Based on statistical research findings, it has been determined that a significant relationship exists between job crafting and adaptive performance at a significance level of 0.05. Additionally, a significant relationship has been observed between resilience and adaptive performance at the same significance level. Furthermore, it has been established that there is a significant relationship between job crafting and resilience and adaptive performance, also at a significance level of 0.05. Based on recommendations for developers in start-up environments, employees can foster personal growth independently or by enrolling in courses focused on resilience and job creation. Employees can proactively modify workplace settings to enhance their performance, increasing their performance levels and overall job satisfaction.